Development of a Model to Estimate 24‐Hour Urinary Creatinine Excretion. Issue 5 (27th March 2014) - Gerber, Linda M.; Mann, Samuel J.
<x xml:space="preserve">Abstract</x> The accuracy of the spot urine analyte/creatinine ratio in estimating 24‐hour excretion of the analyte is compromised because it is not adjusted for 24‐hour creatinine excretion. The authors developed a model for conveniently estimating 24‐hour creatinine excretion. The model was derived from 24‐hour urine collections using multiple linear regression, including sex, weight, race, and age. The model was then evaluated in a validation cohort, assessing the correlation between estimated and measured 24‐hour creatinine excretion and by comparing their correlation with muscle mass. Estimated creatinine excretion correlated strongly with measured creatinine excretion (r=0.80 in the entire cohort and 0.93 after eliminating patients with incomplete collections), and correlated at least as strongly as measured creatinine excretion with lean muscle mass (r=0.94 vs r=0.82, respectively). Adjusting spot urine analyte/creatinine ratios using the estimated 24‐hour creatinine excretion by this convenient method can improve the accuracy of estimating 24‐hour excretion of albumin, sodium, and other analytes.